Yowamushi pedal. 16 - Watanabe, Wataru, 1971- (Yen Press, 2020)
"When two talented new first years join Sohoku's Cycling Club, Sugimoto starts feeling the pressure. To challenge himself and reaffirm his place on the team, he joins the first year race! Meanwhile, Onoda struggles with his new role as both an upperclassman and the champion of the Inter-High...Will Onoda and Sugimoto overcome their challenges and create a stronger Sohoku?!"--Provided by publisher.